Opinions on dynamic topology reconfiguration of distribution networks for PV hosting capacity enhancement - Pei, Zhigang; Chen, Jiaming; Zhang, Zhiyuan; Liu, Weikang; Yan, Xin; Jin, Yifang (Frontiers in Energy Research, 2024)
This paper investigates on dynamic topology reconfiguration of distribution networks to enhance PV hosting capacity. Firstly, a dynamic topology reconfiguration model of distribution networks considering N-1 security constraints is proposed to accommodate intermittent PV generation, and thus high penetration of renewable resources can be ensured to satisfy operational requirements under both normal and fault conditions with load transfer of feeders. Then, a hosting capacity enhancement strategy is presented to decrease risks of voltage and line overloading with reactive power flexibility of energy storage inverters, and is implemented to enhance the maximum hosting capacity of distributed renewable energy sources. Finally, simulation results have validated the effectiveness of the proposed method for PV hosting capacity enhancement of distribution networks.